PENDAMPINGAN PENYUSUNAN SISTEM AKUNTANSI PADA UKM PENGOLAHAN SUSU - Eny Suprapti; Aniek Rumijati (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
IbM aims to assist partners in order to have a reliable accounting information systems that can provide vital information accurately and timely. Therefore, owners and interested parties can analyze and make the right decisions. This system is expected to help owners evaluate the performance and business developments. Partner companies (CV Brawijaya Dairy Industry and CV Karya Brawijaya) want to have a good accounting information system. Accounting information produced is very useful in business planning, product marketing development, performance evaluation and expand access to funding. Therefore, they require the role of internal (company) and external (banks and the Tax Office).These expectations can not be realized because of the partner company faced several obstacles. Constraints are the company does not have the human resources that have the educational background of accounting, facilities and infrastructure (hardware and software) was minimal, limited capital so it will merektur specialized employees handle bookkeeping is still difficult financially. Expansion of product marketing needs to be done so that the product more known to the public. The partner company (CV Karya Brawijaya) has difficulty in determining how much tax should be paid. Tax Office (KPP) is always sent warning letters because partners are often late in paying taxes. It’s happen because the company still does not have a simple bookkeeping and financial statements.Team devotion perform some activity. First; sharing with the leadership of the company to analysis the transaction. Second; preparing accounting software in accordance with the information needs of UKM (based SAK ETAP). Third; providing the necessary facilities and infrastructure (notebook). Fourth; preparing UKM accounting handbook. Fifth; conducting inhouse training for employees who handle bookkeeping and accounting. Sixth; implementation of accounting software and mentoring. Seventh; marketing assistance and tax calculation and how to fill out SPT.